Exotic aquatic organisms in Asia proceedings of a workshop on introduction to exotic aquatic organisms in Asia. - De Silva, S.S. (Manila, Philippines Asian Fisheries Society, 1989)
Asian Fisheries Society ; no. 3
Keywords: Fisheries; Asia; Exotic aquatic organisms